2005
DOI: 10.1063/1.1856224
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the carbon-related “blue” luminescence in GaN

Abstract: The properties of a broad 2.86 eV photoluminescence band in carbon-doped GaN were studied as a function of C-doping level, temperature, and excitation density. The results are consistent with a C Ga -C N deep donor-deep acceptor recombination mechanism as proposed by Seager et al. For GaN:C grown by molecular-beam epitaxy (MBE) the 2.86 eV band is observed in Si co-doped layers exhibiting high n-type conductivity as well as in semi-insulating material. For low excitation density (4 W/cm 2 ) the 2.86 eV band in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 24 publications
11
46
0
Order By: Relevance
“…Lyons et al [9] calculated that optical transitions of electrons from the conduction band to this level would cause a blue band with a maximum at about 2.7 eV. These authors noticed that in C-doped GaN, a blue band is often observed when the carbon concentration is high [10,11], or at high excitation intensity [12,13], which, in their opinion, supported the existence of the 0/+ level of the C N defect. In contrast, there is only one optically active transition level for the C N O N complex in the band gap of GaN.…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 60%
See 3 more Smart Citations
“…Lyons et al [9] calculated that optical transitions of electrons from the conduction band to this level would cause a blue band with a maximum at about 2.7 eV. These authors noticed that in C-doped GaN, a blue band is often observed when the carbon concentration is high [10,11], or at high excitation intensity [12,13], which, in their opinion, supported the existence of the 0/+ level of the C N defect. In contrast, there is only one optically active transition level for the C N O N complex in the band gap of GaN.…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 60%
“…A careful analysis suggests that this is unlikely. Indeed, a blue band is often observed in C-doped GaN, along with the YL band [10][11][12][13]46]. However, closer inspection of the luminescence spectra in these papers allows us to conclude that at least two different defect-related blue bands were observed.…”
Section: A Yellow and Blue Luminescence Bands In Undoped And C-dopedmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous DLOS and photoluminescence studies of defects in bulk GaN have correlated defect levels near mid-gap and near the valence band to carbon-related defects. [23][24][25][26][27] Carbon is an expected interface impurity due to exposure to atmosphere before the ALD process, and due to the presence of carbon in the aluminum precursor (i.e. TMAl).…”
Section: Resultsmentioning
confidence: 99%